Ammonium [(1S)-(endo,anti)]-(-)-3-bromocamphor-8-sulfonate - Abbasi, M.A.; Aziz, Ur-Rehman; Akkurt, M.; Jahangir, M.; Ng, S.W.; Khan, I.U. (International Union of Crystallography, 2010)
In the title molecular salt, NH(4)(+)center dot C(10)H(14)BrO(4)S(+), the norbornane skeleton of the anion is composed of two five-membered rings in envelope conformations and a six-membered ring with one Br atom, one carbonyl O atom and a methyl group held in a boat conformation by a bridging methylene group. Short intramolecular C-H center dot center dot center dot O and C-H center dot center dot center dot Br interactions occur. In the crystal, the component ions are linked by intermolecular N-H center dot center dot center dot O and C-H center dot center dot center dot O hydrogen bonds.